2023
DOI: 10.1002/ps.7654
|View full text |Cite
|
Sign up to set email alerts
|

Host plant recognition by two odorant‐binding proteins in Rhynchophorus ferrugineus (Coleoptera: Curculionidae)

Abstract: BACKGROUNDRhynchophorus ferrugineus, the red palm weevil (RPW), is a key pest that attacks many economically important palm species and that has evolved a sensitive and specific olfactory system to seek palm hosts. Odorant‐binding proteins (OBPs) not only play crucial roles in its olfactory perception process but are also important molecular targets for the development of new approaches for pest management.RESULTSAnalysis of the tissue expression profiles of RferOBP8 and RferOBP11 revealed that these two Rhync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…In R. ferrugineus, silencing RferOBP8 and RferOBP11 reduced preference for eight plant volatiles by Y-tube-choice behavioral assay. 33 In D. helophoroides, RNAi-mediated of DhelOBP4 lost the trend to γterpinene and p-cymene in Y-tube olfactometer bioassays. 46 Silencing HparOBP3 by the injection of dsRNA, the antennal electrophysiological responses and preference to compounds significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In R. ferrugineus, silencing RferOBP8 and RferOBP11 reduced preference for eight plant volatiles by Y-tube-choice behavioral assay. 33 In D. helophoroides, RNAi-mediated of DhelOBP4 lost the trend to γterpinene and p-cymene in Y-tube olfactometer bioassays. 46 Silencing HparOBP3 by the injection of dsRNA, the antennal electrophysiological responses and preference to compounds significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In R. ferrugineus, silencing RferOBP8 and RferOBP11 reduced preference for eight plant volatiles by Y-tube-choice behavioral assay . In D.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicating that PverOBP18 may play an important role in various biologic processes during the life stage of P. versicolora. Usually, the majority of OBP genes are found to be expressed in chemosensory organs of insectile adults, including the antennae, maxillary palp and proboscis, such as P. versicolora ( Liu et al., 2021 ), Tribolium castaneum ( Dippel et al., 2014 ) and Rhynchophorus ferrugineus ( Huang et al., 2023 ). Previous study had found that PverOBP18 was mainly expressed in the antennae of adult P. versicolora when compared to other tissues, indicating the similar chemoreception function in P. versicolora ( Liu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%